The Effects of Low Altitude Training on Erythropoietin Response and Hematological Variables in Elite Female Fencers - Volkan Gürses, Veli; Şakir Akgül, Mustafa (Horizon Research Publishing Co., Ltd., 2018)
The Live High-Train High (LHTH) model altitude training is required to sojourn over 2000m more than 3 weeks. In such altitudes response that may cause decreased living, sleeping and training quality. In these cases coaches may approach with suspicion to LHTH can be harmful for their training intensity edgewise training quality. The aim of this study was to investigate the effect of 12 days 1850m training on some hematological parameters in the world-class woman fencers. Ten female fencers (age 21.50 ± 3.69, height 167.16 ± 3.88 cm, weight 59.11 ± 3.437 kg) voluntarily participated in this study. The athletes were investigated low altitude training camp at 1850m. The blood samples were taken before and after the moderate altitude training for analyzing erythropoietin (EPO), red blood cell (RBC), hemoglobin (HB) and hematocrit (HCT) concentration levels. The paired sample t-test was used for determine the differences pre and posttests results, significance levels p<0.05 Results shows that concentrations of EPO increased significantly after twelve days low altitude training. However RBC, HB, HCT concentrations were unaffected by the hypoxic stimulus. The results of this study have suggested that the 12 days LHTH training at 1850 m can be stimulated EPO. This means 1850 m altitude possibly induces hypoxic effect. Nevertheless, 12 days altitude training is not enough to enhance performance related blood markers.